Identificação de ligantes e substratos do complexo E3 ubiquitina-ligase SCF(FBXL17) - Passos, Patrícia Maria Siqueira dos (Universidade Federal de São Carlos, 2022)
Fbxl17 is one of the 69 F-box (Fbx) proteins in humans capable of interaction with SKP1, Cullin 1 and Rbx1 to form the E3 ubiquitin ligase complex SCF(Fbxl17). The SCF(Fbxl17) complex is the major class of human E3 ubiquitin-ligases and acts ubiquitylating its substrates leading them either to proteasome degradation or function modulation. The Fbxls proteins have a F-box domain that interacts with SKP1 and a LRR domain (Leucine Rich Repeat domain) for substrate interaction. This LRR domain gives specificity to the SCF(Fbxl17) complex. In the METABRIC project (Molecular Taxonomy of Breast Cancer International Consortium) mutations in FBXL17 were found leading to depletion in the LRR domain of Fbxl17 protein. Those mutations were identified in 135 out of 1992 patient’s samples. Moreover, it was performed a CGH-array (Comparative Genomic Hybridization) of 746 cancer cell lines. As a result, they identified breaks in the FBXL17 gene in 3 cell lines of breast cancer (BT-474, HCC38 and HCC1395) and in 1 cell line of esophageal/gastric cardia adenocarcinoma (OE-19). Those breaks led to the generation of Fbxl17 protein with LRR domain truncation, among those mutants there is a protein entitled Fbxl17-Δ3LRR. Since there are no study relating Fbxl17 to tumorigenicity, we aimed to identify potential substrates for Fbxl17. It was performed an immunoprecipitation assay to purify SCF(Fbxl17), SCF(Fbxl17-Δ3LRR) and Fbxl17-ΔF-box from HEK293T cells. The eluates were submitted to a large-scale in vitro ubiquitination assay (Protoarray). We were able to identify 194 possible substrates positive for SCF(Fbxl17) excluding the ones that were detected in the Fbxl17-ΔF-box slide, and 92 targets that were positive only for SCF(Fbxl17) subtracting the ones that were positive for SCF(Fbxl17-Δ3LRR) and Fbxl17-ΔF-box. With those data, a functional enrichment analysis was performed using REACTOME and DAVID databases. The data showed most targets were related to RNA metabolism regulation and several of them were associated to splicing processing. Therefore, a functional assay was performed to evaluate whether Fbxl17 plays role in pre-mRNA splicing. It was used a splicing reporter minigene called E1A in two different cell lines (HEK293 and MCF7). Afterwards, several targets were selected to go through substrate validation analysis. After performing interaction and ubiquitylation assay in cell, it was observed that DDB1, SNRPB2, and SRS9 interact with Fbxl17. Moreover, among those binders our data indicate that DDB1 is ubiquitylated by SCF(Fbxl17) in cells. Hence, this study identified three new binders to Fbxl17 and one novel substrate. The functional characterization and the relationship of those binders to tumor development are going to be evaluated in subsequent study.
Identification of binders and substrates of the E3 ubiquitin-ligase SCF(Fbxl17) complex
Keywords: Ubiquitinação; Câncer; SCF(Fbxl17); Ubiquitylation; Cancer; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR